A conception with congenitally complicated connection: a rare case of pregnancy with total anomalous pulmonary venous connection - P., Priyadarsene; M., Mahalakshmi; R., Sangeetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Total anomalous pulmonary venous connection (TAPVC) is a congenital cyanotic heart disease characterized by abnormal communication of pulmonary veins into the right atrium rather than into the left atrium leading to mixture of oxygenated and deoxygenated blood. Uncorrected TAPVCs do not survive till adulthood and pregnancy in patients with TAPVC is extremely rare. In patients with TAPVC, the heart cannot withstand the hemodynamic changes associated with pregnancy and hence termination of pregnancy in the first trimester is often required. Here we reported an extremely rare case of pregnancy in a patient with uncorrected TAPVC, terminated successfully in our institute without any complication.